IMPLEMENTASI MANAJEMEN LABORATORIUM TKJ DI SMK MUHAMMADIYAH PAGELARAN PRINGSEWU - Gusliana, Evi (STIT PRINGSEWU, 2024)
This article examines how the inmplementation of management from a laboratory at SMK Muhammadiyah Pagelaran sees from how the initial planning is carried out from the planning process for determining laboratory prutas, planning the schedule of laboratory activities, to the procurement planning process, organizing so that the guidance of laboratory management is achieved, the implementation carried out by laboratory officers must be in accordance with their responsibilities so that the management process runs in accordance with its function and the supervision carried out to find out how the suitability and problems that occur when laboratory management occurs. The purpose of this research is to find out how the implementation is carried out in the laboratory of SMK Muhammadiyah Pagelaran, this article uses a research method using interviews with direct speakers and direct observation on the object of research. From this research, it was found that the management carried out in the laboratory of SMK Muhammadiyah Pagelaran has been good with the creation of the laboratory structure, management decree, competent laboratory officers, supervision that has been carried out, but there are several things that need follow-up improvement in terms of the implementation of responsibilities, the procurement process and maintenance of practical equipment. Keywords : Implementation, Management, Laboratory